Prognostic Role of Neutrophil to Lymphocyte Ratio (NLR) in Stage IV Non-Small Cell Lung Cancer (Journal of Fatima Jinnah Medical University, 2025)
Background: Neutrophil to lymphocyte ratio has emerged as potential biomarker for cancer prognosis due to its accessibility and ease of calculation using routine blood- cell counts. Patients of non-small cell lung cancer (NSCLC) with higher neutrophil to lymphocyte ratio (NLR) before treatment have worse prognosis than those patients who have lower neutrophil to lymphocyte ratio (NLR). The objective of this study is to evaluate the prognostic role of neutrophil to lymphocyte ratio (NLR) in stage IV non-small cell lung cancer.Patients and methods: This prospective cohort study was conducted from 8th January to 8th July 2023 in the indoor Pulmonology Department at KEMU, Lahore, in collaboration with the Oncology Department. A total of 114 biopsy-confirmed, treatment-naïve stage IV NSCLC patients aged 40–80 years were enrolled using non-probability consecutive sampling. Patients with prior treatment or active infections were excluded. Study parameters included age, gender, baseline NLR (≤3.5 or ≥3.5), and survival at 6 and 12 months. Data were collected using a structured proforma from patient records and laboratory reports. NLR was calculated from baseline CBC. Statistical analysis was performed using SPSS v26; independent t-tests were used to compare survival outcomes, with p
Keywords: Neutrophil; Lymphocyte; Ratio; Stage IV; Non-small cell lung cancer; prediction; prognostic marker